Problem Based Learning (PBL) Berbantuan Educaplay : Pengaruh terhadap Kemampuan Berpikir Kritis Siswa Kelas XI SMAN 2 Samarinda - Utami, Khairida Kanaya; Masitah, Masitah; Kurniawati, Zenia Lutfi; Maasawet, Elsje Theodora; Makkadafi, Suparno Putera; Akhmad, Akhmad (Biocaster : Jurnal Kajian Biologi, 2025)
This study aims to determine the effect of the Problem Based Learning (PBL) learning model using Educaplay media on the critical thinking skills of class XI students of SMA Negeri 2 Samarinda in the 2024/2025 academic year. This type of research is quasi-experimental using a non-equivalent control group design. Sampling in this study used a purposive sampling technique with a sample size of 26 students each for the experimental class and the control class. The data analysis techniques used were the N-Gain test and the independent sample t-test. The results of the data analysis showed that the N-Gain value of critical thinking skills of students in the experimental class with an average of 0.41 was included in the moderate category, and the control class was 0.32 in the moderate category. The results of the hypothesis showed a sig. (2-tailed) value of 0.028 (<0.05) for critical thinking skills, where the sig. value. (2-tailed) <0.05 so it can be concluded that the Problem Based Learning (PBL) learning model using Educaplay media has a significant effect on the critical thinking skills of class XI students of SMA Negeri 2 Samarinda. This finding shows that the integration of PBL with digital interactive media can be an effective alternative to improve students' critical thinking skills.